2016
DOI: 10.1371/journal.pone.0165746
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Response of Listeria monocytogenes to Heat, Salinity and Low pH, after Habituation on Cherry Tomatoes and Lettuce Leaves

Abstract: Pathogens found on fresh produce may encounter low temperatures, high acidity and limited nutrient availability. The aim of this study was to evaluate the effect of habituation of Listeria monocytogenes on cherry tomatoes or lettuce leaves on its subsequent response to inhibitory levels of acid, osmotic and heat stress. Habituation was performed by inoculating lettuce coupons, whole cherry tomatoes or tryptic soy broth (TSB) with a three-strains composite of L. monocytogenes, which were further incubated at 5°… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 59 publications
1
18
0
1
Order By: Relevance
“…Listeria monocytogenes is a pathogen responsible for listeriosis, a foodborne disease with high mortality rates among the immunecompromised individuals, pregnant women, neonates and the elderly. In healthy individuals, it generally can cause self-limiting febrile gastroenteritis (Ferreira & Domingues, 2016;Poimenidou et al, 2016). There is a broad range of food products that pose a risk of L. monocytogenes dissemination, which, together with its ability to survive and develop tolerance to stress, makes it possible to persist in diverse environments.…”
Section: Introductionmentioning
confidence: 99%
“…Listeria monocytogenes is a pathogen responsible for listeriosis, a foodborne disease with high mortality rates among the immunecompromised individuals, pregnant women, neonates and the elderly. In healthy individuals, it generally can cause self-limiting febrile gastroenteritis (Ferreira & Domingues, 2016;Poimenidou et al, 2016). There is a broad range of food products that pose a risk of L. monocytogenes dissemination, which, together with its ability to survive and develop tolerance to stress, makes it possible to persist in diverse environments.…”
Section: Introductionmentioning
confidence: 99%
“…Low temperatures are commonly used in food production, and the adaptive mechanisms developed by L. monocytogenes that allow its proliferation at low temperatures have been reviewed (Tasara and Stephan, 2006). Poimenidou et al (2016) showed that the habituation of L. monocytogenes on different fresh produce surfaces resulted in differential responses to acid, osmotic, and temperature stressors, and that the habituated cells demonstrated increased resistance to stressors compared with cells grown in laboratory media. In the current study, we assessed the long-term survival of artificial and in-process L. monocytogenes contaminants in ice cream scoops at −20°C.…”
Section: Short Communicationmentioning
confidence: 99%
“…Listeria monocytogenes can survive and persist on lettuce leaf surfaces in different conditions (Poimenidou et al ., ). Murphy et al .…”
Section: Introductionmentioning
confidence: 97%
“…The ability of many strains of L . monocytogenes to be able to withstand harsh food environments such as high salt concentration, low oxygen and high acidity has been reported (Poimenidou et al ., ). After L .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation